2015
DOI: 10.1080/09540121.2015.1113227
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and disease outcomes of migrants from low- and middle-income countries in the Australian HIV Observational Database cohort

Abstract: People from culturally and linguistically diverse backgrounds, including low- and middle-income countries, account for a third of new HIV diagnoses in Australia and are a priority for HIV prevention and treatment programs. We describe the demographic and clinical characteristics of participants in the Australian HIV Observational Database (AHOD) and compare disease outcomes, progression to AIDS and treatment outcomes of those born in low- and middle-income countries, with those born in high-income countries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Individuals diagnosed with HIV under 25 years of age in Australia were predominantly male, although a greater proportion of newly diagnosed young adults were females compared to their older counterparts. In part these figures reflect overall trends in Australia with an increasing but relatively small proportion of women diagnosed with HIV, and they are also reflective of migration trends in Australia . In our cohort, male‐to‐male sexual contact was the predominant risk factor for HIV acquisition in both groups, and most received their HIV care at publicly funded sexual health clinics.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Individuals diagnosed with HIV under 25 years of age in Australia were predominantly male, although a greater proportion of newly diagnosed young adults were females compared to their older counterparts. In part these figures reflect overall trends in Australia with an increasing but relatively small proportion of women diagnosed with HIV, and they are also reflective of migration trends in Australia . In our cohort, male‐to‐male sexual contact was the predominant risk factor for HIV acquisition in both groups, and most received their HIV care at publicly funded sexual health clinics.…”
Section: Discussionsupporting
confidence: 53%
“…In part these figures reflect overall trends in Australia with an increasing but relatively small proportion of women diagnosed with HIV, 18 and they are also reflective of migration trends in Australia. 19 In our cohort, male-to-male sexual contact was the predominant risk factor for HIV acquisition in both groups, and most received their HIV care at publicly funded sexual health clinics. Risk factors were similar to US data in 2014, where 70% of HIV infection in adolescents and young adults was attributed to male to male sexual contact.…”
Section: Treatment and Outcomesmentioning
confidence: 84%
“…In the literature, there are few studies that compare the differences between the developmental levels and incidence of TB and other infectious diseases in various countries [1,[4][5][6]. We did not find any existing study investigating the relationship between TB incidence and all detailed HDI parameters.…”
Section: Introductionmentioning
confidence: 48%
“…In our study, neither of these variables were associated with CKD across the board after adjusting for other factors. This may be explained by high rates of ART uptake across the cohort and low prevalence of patients of African descent in the AHOD population . Interestingly, analysis of those aged over 50 years in our study showed low CD4+ count and high viral load to be significant risk factors for CKD.…”
Section: Discussionmentioning
confidence: 99%